Occupational asthma and rhinitis due to wheat flour: sublingual specific immunotherapy treatment - Dubini, Marco; Marraccini, Paolo; Brass, David M.; Patrini, Lorenzo; Riboldi, Luciano (La Medicina del Lavoro, 2020)
Background: There are several potential sensitizers in the bakery environment and wheat flour appears to be the dominant sensitizer in most bakeries. Apart from traditional drug therapy or a change in profession, there are no effective therapies for workers who develop serious respiratory symptoms in the workplace. Objectives: To describe clinical and laboratory findings in workers with asthma and/or rhinitis induced by wheat flour who underwent sublingual specific immunotherapy (SLIT). Methods: Since drug therapy and prevention strategies were not effective, five bakers were elected to undergo SLIT. A three-year study was led by administering a sublingual wheat flour extract. Questionnaires, allergy and respiratory tests were performed before and after SLIT. Results: After SLIT an improvement in symptoms is observed in every patient: Asthma Control Test and a quality-of-life questionnaire show higher scores and as a result, workers have reduced the use of drug therapy. We observed significantly reduced exhaled nitric oxide (FeNO) and eosinophil cationic protein (ECP) levels after SLIT, hypothesizing that these parameters may be used to monitor the effectiveness of immunotherapy. The improvement of FEV1 (forced expiratory volume in 1second) and responsiveness to bronchoprovocative tests with methacholine denotes a possible role of SLIT in treating patients with low-respiratory tract involvement, even though more data are needed. Discussions: This is the first report in the literature on the use of SLIT for baker’s asthma and rhinitis. SLIT for occupational wheat flour allergy should be possible and efficient, saving vocational training, professionalism, and avoiding job loss.